Health Information Security Guidelines for Healthcare Information Systems - Narayanan Samy , Ganthan; Ahmad , Rabiah; Ismail , Zuraini (2011)
This paper aims to proposed appropriate information security guidelines for healthcare organization. A study has been carried out in one of government supported hospital in Malaysia. The hospital has been equipped for a Patient Management System (PMS). The data were collected from various departments and wards using semi-structured interviews. The study shows several most critical threats for the PMS which includes technical and non technical factors based on predefined information security threats categories in Healthcare Information Systems (HIS). Although there is similarity set of threats categories found as previous research but the authors provides relevant information security guidelines particularly for HIS. Thus, this research holds significant value in terms of providing appropriate information security guidelines for information security practitioners, healthcare practitioners and for healthcare top management authorities in order to manage their HIS effectively.